Development and comparison of various rod-shaped mini-reference electrode compositions based on Ag/AgCl for potentiometric applications - Nigde, Mustafa; Agir, Ismail; Yildirim, Ridvan; Isildak, Ibrahim (ROYAL SOC CHEMISTRY, 2022)
Several fundamentally similar, miniaturized solid-state reference electrode designs, and their fabrication and comparison are described in this article. All electrodes were based on Ag/AgCl as their reference element. The best electrode (a three-layer assembly with graphite oxide, epoxy, and hardener as the framework providers and with well-mixed micro-Ag particles in the bottom layer, AgCl in the middle layer, and fine KCl powder in the top layer) exhibited satisfactory short-term performance to replace a commercial reference electrode in many cases and was rigorously tested in terms of pH response, long-term leakage, and the effect of oxygen to better evaluate its characteristics. To assess the electrode's performance in medically important studies, cytotoxicity experiments and tests in artificial saliva were also conducted. All tests demonstrated that our best reference electrode was stable and had a long shelf life.
Keywords: STATE REFERENCE ELECTRODES; POLYMER; CHIP; PH; Chemistry